2004
DOI: 10.1007/s00431-004-1488-8
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal skin colour changes in term newborns with subclinical histological chorioamnionitis

Abstract: These findings, compatible with early peripheral microcirculatory changes, indicate skin vasoconstriction as an early neonatal manifestation of subclinical chorioamnionitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The high level of expression of MHC genes in all samples from P32, including amnion, cord, and villus sections, suggests an inflammatory process in this placenta, although, clinically it was considered to be healthy and free of infection. Studies have found subclinical chorioamnionitis, which was discovered incidentally during histopathology of placenta from clinically noninfected women (30). Unfortunately, no samples of the P32 placenta were available for histological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The high level of expression of MHC genes in all samples from P32, including amnion, cord, and villus sections, suggests an inflammatory process in this placenta, although, clinically it was considered to be healthy and free of infection. Studies have found subclinical chorioamnionitis, which was discovered incidentally during histopathology of placenta from clinically noninfected women (30). Unfortunately, no samples of the P32 placenta were available for histological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our prior research has generated several early markers for HCA in specific, selected high-risk neonatal categories (22,28,29) and identified HCA as a major predictor of morbidity and mortality among VLBW newborns.…”
Section: Discussionmentioning
confidence: 99%
“…These current limitations have stimulated a search for new, real-time indices of neonatal severity based on different concepts. We have previously assessed the potential value of skin colorimetry (33,34), skin spectrophotometry (35), and pulse oximetry-derived PI (19,21) in identifying different categories of higher-severity newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the neonatal population have highlighted the potential for PI to be used as an assessment tool in various aspects of an infant's health [6]. In particular, studies have associated PI in the newborn period with subclinical chorioamnionitis [7], as a possible screening tool for the presence of congenital heart malformations [8,9], as a predictor of low superior vena cava flow [10], and as a sign of improved tissue …”
Section: Introductionmentioning
confidence: 99%